CAMEL Ratio: An Approach To Measuring The Health Of Financial Institutions - Dina Amaluis; Hayu Yolanda Utami (Universitas Negeri Padang, 2019)
This research aims at finding out the differences of health level of Financial Institution by using CAMEL. The magnitude of the potential financial institutions make profits in the segment of small and micro finance as a market for rural banks (BPR), especially Islamic rural banks (BPRS).. The level of Bank efficiency could be integrated with the performance of banks which was adopted from Central Bank (BI) criterias, namely CAMEL (Capital, Asset Quality, Management, Earnings and liquidity).